Correlation of manometric, oesophagoscopic, and radiological findings in the columnar-lined gullet (Barrett syndrome). Issue 4 (December 1963) - Cohen, B. R.; Wolf, B. S.; Som, M.; Janowitz, H. D.
Abstract : An intensive study has been made of the columnar-lined gullet (Barrett syndrome) and in the patient described it was shown to have the motor characteristics of the body of the oesophagus. At the distal end there was the normal receptive relaxation with swallowing. There was no discontinuity between the squamous and the columnar-lined portions.